Apostates as a Hidden Population of Abuse Victims - Egan, Vincent (2021)
The term “apostate” describes the term used by the religious to describe individuals raised within religious families who once identified as religious, but who have ceased to believe in the existence of God, gods or follow their religious belief, and now identify as non-religious. Given the strong feelings families can have about the rejection of their shared faith, and the difficulty that police forces may have in identifying and understanding the complexities of violence toward the apostate, this study sought to examine the possibility that apostates represent a hidden population of abuse victims within religious households. We recruited 228 persons (102 males, 119 females) from an online survey with the support of “Faith to Faithless”—a service within Humanists UK, which supports people that leave their religious faith. Individuals were screened using a modified version of the Conflict Tactics Scale to quantify their experience of assault and negotiation. It was found that persons who identified as apostates experienced more assault (i.e., harmful violence) than non-religious persons. Within this sample, Muslim apostates were significantly more likely to be victimized than Christian apostates. Disclosure of being abused for identifying as an apostate within a religious household to law enforcement was extremely uncommon, thereby preventing detection or prosecution of abusive acts committed by family members and limiting public awareness of this issue. These results are discussed in the context of the broader culture of honor-based (izzat) violence, which occurs across the Eastern Mediterranean, Middle East, and North Africa, and is also seen in some Protestant Christian subcultures, and common to all Abrahamic religions, rather than Islam alone. This study highlights that within a multicultural society, there remain hidden populations of abuse victims who are vulnerable due to religious, cultural, and traditional constraints made by abusive family members